Acousto-optic characterization of bending damage of pre-cut steel-polyvinyl alcohol hybrid fiber reinforced concrete - Guoliang Yang; Zhiwen Dong; Tongde Zhao; Kangpu Zhao; Jianyu Zhao; Wei Ye (Case Studies in Construction Materials)
This study investigates the flexural mechanical properties of pre-cracked steel-polyvinyl alcohol (PVA) hybrid fiber-reinforced concrete beams with varying fiber contents. Hybrid fiber composite materials were utilized, with PVA fiber volume fraction at 1.5 % and steel fiber volume fractions ranging from 0 % to 1.5 %. Three-point bending tests were conducted using an MTS hydraulic servo test system, supplemented by Digital Image Correlation Method (DICM) and Acoustic Emission (AE) technology, to analyze changes in surface strain fields and the development of internal microcracks. Results indicate that the peak strength of the steel-PVA hybrid fiber-reinforced concrete beams increases linearly with the steel fiber content. The ultimate flexural strength reaches a maximum of 5.89 MPa when the steel fiber content is 0.9 % and the PVA fiber content is 1.5 %. However, increasing the steel fiber content beyond 0.9 % diminishes the toughening effect. The addition of steel fibers (SF) reduces the proportion of shear failure within the specimen during loading and makes the release of crack strain energy more dispersed and uniform. At an SF content of 1.2 %, the calculated horizontal strain on the specimen surface is minimized, suggesting that this fiber content is less likely to cause instability failure under the same loading conditions. The theoretical length of the fracture process zone for the concrete beams ranges from 8.77 to 23.12 mm, while the measured length ranges from 10.42 to 20.05 mm, showing good agreement with theoretical values. These findings enhance the understanding of crack initiation and propagation mechanisms in steel-PVA hybrid fiber-reinforced concrete and provide theoretical guidance for designing performance-based hybrid fiber-reinforced cement-based composite materials.